Effect of Different Types of Bait in Collapsible Traps Gear on Mangrove Crab (Scylla serrata) Catches in Kampung Laut Waters - Sumantri, Abdi Vico; Pramusintho, Bagus; Ramadan, Fauzan (Faculty of Fisheries and Marine, Universitas Riau, 2023)
Mangrove crab (Scylla serrata) catching activities generally use collapsible traps. collapsible traps can be operated using bait and not using bait but the catch is less effective if it does not use bait. The purpose of this study was to determine the effect of using different types of bait (fresh stingray, salted stingray, fresh eel, and salted eel) on the catch of mangrove crab in Kampung Laut waters. The material of this research is the catch of mangrove crabs using fresh stingrays, salted stingrays, fresh eels, and salted eels as bait. The research method used is experimental fishing. The data collected includes environmental parameters, the total number of catches, and the size of the catch. Data analysis used a completely randomized design (CRD) and Duncan's follow-up test. The results showed that the different types of bait used had an effect on the number of catches, catch weight, and catch size. This study concludes that the catch of mangrove crabs with salted stingray bait gets the most catches, namely 16 fish, and on salted eel bait gets 13 catches while fresh stingray bait treatment only gets 7 catches and on fresh eel gets 5 catches.